Are circadian rhythms more favorable with lithium than with other mood stabilizers? An exploratory actigraphy study in euthymic bipolar disorder type 1 - Vincent Hennion; Jan Scott; Victoire Martinot; Chloé Benizri; Cynthia Marie-Claire; Frank Bellivier; Bruno Etain (Comprehensive Psychiatry)
Background: Bipolar Disorder (BD) is associated with alterations of circadian rhythms of activity (CRA). Experimental research suggests that lithium (Li) modifies CRA, but this has been rarely explored in BD using actigraphy. Methods: The sample comprised 88 euthymic BD-I cases with 3 weeks of actigraphy. We used a Principal Component Analysis (PCA) to generate CRA dimensions. We then used linear regression analyses to compare these dimensions between groups of individuals defined according to prescribed mood stabilizers: Li monotherapy (“Li” group, n = 28), anticonvulsant or atypical antipsychotic monotherapy (“AC or AAP” group, n = 27) or combined treatments (“Li+AC or Li+AAP” group, n = 33). Analyses were adjusted for potential confounders (gender, age, body mass index, depressive symptoms, co-prescribed benzodiazepines and antidepressants, smoking status and past alcohol use disorder). Results: The PCA identified two dimensions: “robust CRA” (high amplitude and interdaily stability, with low intradaily variability) and “late chronotype”. Univariate analyses showed higher scores for “robust CRA” in the “Li” versus the “AC or AAP” (p = 0.021) or “Li+AC or Li+AAP” groups (p = 0.047). These findings remained significant after adjustments (respectively p = 0.010 and p = 0.019). Post-hoc analyses suggested lower variability, higher stability and higher amplitude of CRA in the “Li” group. Medication groups were similar for the “late chronotype” dimension (p = 0.92). Conclusions: This actigraphy study is the first to show more favorable CRA in BD-I individuals receiving a Li monotherapy when compared with those receiving other classes or combinations of mood stabilizers. Replications in larger samples are required. Prospective studies are also warranted to elucidate whether the introduction of Li or other mood stabilizers might influence CRA in BD-I.